2001
DOI: 10.1097/00006231-200106000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Post-stress end-systolic left ventricular dilation: a marker of endocardial post-ischemic stunning

Abstract: Several studies have shown the accuracy of gated single photon emission computed tomography (SPECT) using thallium-201 and technetium tracers in the assessment of myocardial perfusion and function. Gated SPECT has been successfully utilized to detect post-stress left ventricular ejection fraction (LVEF) reduction resulting from post-ischemic stunning in patients with coronary obstruction. The aim of this study was to evaluate whether the post-stress LVEF impairment could be related to the post-stress end-systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 30 publications
2
44
0
4
Order By: Relevance
“…[1][2][3] In the studies about poststress gated SPECT functional changes, the time interval between tracer injection and poststress imaging ranged from 15 minutes to more than 60 minutes, and there was no direct comparison between different delays. 1,2,[19][20][21][22][23][24][25][26][27][28] Recently, Toba et al 3 reported that in patients with single-vessel CAD, a very early (10 minutes) poststress gated SPECT study was superior to the usual 30-and 50-minute intervals to identify transient decreases in EF in the subjects with stress-induced ischemia, and they confirmed the relationship between severity of ischemia and degree of functional impairment. To our knowledge, their study is the only one addressing the issue of ischemiarelated functional changes by comparing different acquisition delays.…”
Section: Acquisition Delay and Ischemia-related Functional Changesmentioning
confidence: 96%
“…[1][2][3] In the studies about poststress gated SPECT functional changes, the time interval between tracer injection and poststress imaging ranged from 15 minutes to more than 60 minutes, and there was no direct comparison between different delays. 1,2,[19][20][21][22][23][24][25][26][27][28] Recently, Toba et al 3 reported that in patients with single-vessel CAD, a very early (10 minutes) poststress gated SPECT study was superior to the usual 30-and 50-minute intervals to identify transient decreases in EF in the subjects with stress-induced ischemia, and they confirmed the relationship between severity of ischemia and degree of functional impairment. To our knowledge, their study is the only one addressing the issue of ischemiarelated functional changes by comparing different acquisition delays.…”
Section: Acquisition Delay and Ischemia-related Functional Changesmentioning
confidence: 96%
“…11,12 Others explain it by a stress-induced subendocardial hypoperfusion giving the visual impression of dilatation on ungated SPECT. 13,14 Nonetheless, the severity of post-ischemic stunning differs between the different stress agents: it seems that myocardial dysfunction persists much longer after dobutamine than after See related article, https://doi …”
mentioning
confidence: 99%
“…11,12 Others explain it by a stress-induced subendocardial hypoperfusion giving the visual impression of dilatation on ungated SPECT. 13,14 Nonetheless, the severity of post-ischemic stunning differs between the different stress agents: it seems that myocardial dysfunction persists much longer after dobutamine than after adenosine stress. 12,15,16 All these challenges may affect the accurate and reliable estimation of myocardial stunning and could result not only in high inter-and intra-patient variability but also between different SPECT scanners and image acquisition protocols.…”
mentioning
confidence: 99%
“…5,6 According to this explanation, post-stress stunning results in end-systolic volume enlargement of the left ventricle. Since non-gated images used for TID calculation reflect summation of counts originating from the whole cardiac cycle, reduced post-stress ventricular contraction with larger end-systolic volume results in increased non-gated LV volume and increased TID ratio.…”
mentioning
confidence: 99%
“…Since non-gated images used for TID calculation reflect summation of counts originating from the whole cardiac cycle, reduced post-stress ventricular contraction with larger end-systolic volume results in increased non-gated LV volume and increased TID ratio. Betesti et al 5 demonstrated that post-stress LV dilation by gated SPECT reflected endocardial post-ischemic stunning with reduced ejection fraction and thickening score, and was associated with more severe clinical, angiographic, and perfusion parameters. Another investigation supporting this mechanism demonstrated LV dysfunction at stress echocardiography among patients with TID at MPI.…”
mentioning
confidence: 99%